No detection of EBV, BKV and JCV in breast cancer tissue samples in Iran - Razieh Dowran; Negar Joharinia; Akbar Safaei; Sahar Bakhtiyarizadeh; Abootaleb Alidadi Soleimani; Rasool Alizadeh; Sara Mir-Shiri; Jamal Sarvari (BMC Research Notes, 2019)
Abstract Objective The most common cancer amongst women is breast cancer. Reports on the role of EBV, BKV, and JCV in the development of breast cancer are controversial. Hence, the aim of this study was to determine the frequency of EBV, BKV, and JCV in malignant breast tumors in comparison with benign ones. Results A total of 300 breast biopsy tissues were included, of which 150 were malignant and 150 benign. After deparaffinization, tissues were subjected to DNA extraction. β-globin gene was amplified by PCR to evaluate the quality of extracted DNA. In house PCRs assay was performed to detect EBV, JCV, and BKV genome fragment. The mean age of malignant and benign groups was 45.0 ± 9.4 and 35.2 ± 12.1 years old. Out of 150 malignant samples, 146 were ductal, two lobular and two samples both invasive ductal and lobular carcinoma. In the benign group, 96, 52 and two samples were fibroadenoma, fibrocystic, and adenosis types, respectively. Genomic DNA fragment of EBV, BKV, and JCV was not found in any of the malignant and benign breast tissues. Conclusion According to our finding, there is the possibility that EBV, BKV, and JCV are not involved in breast cancer pathogenesis.